Estimate the durability of rice husk ash concrete subjected to sulfate attack through wetting and drying cyclic - Putra Jaya, Ramadhansyah; M. R., Hainin; O., Rokiah; B. W., Chong; W. I., Mohd Haziman; S. A., Mangi (Springer, 2021)
It is well known that aggressive environments like the sulfate attack are the major factor affecting the durability of concrete. Thus, this research was carried out to estimate the durability of rice husk ash (RHA) concrete exposed to sodium sulfate attack through wetting and drying cyclic. Five levels of cement replacement namely 0, 10, 20, 30 and 40% (by weight) were studied. After being kept in the sodium sulfate solution for 3, 7, 28, 56, 90 and 180 days, the RHA concrete specimens were evaluated based on the rapid chloride permeability and its correlation. It was found that the total charge passed in Portland cement concrete was higher than that of RHA-blended cement concrete. However, it continued to decrease along with increasing levels of RHA replacement. In addition, the use of 40% RHA in the cement resulted in better resistance to sulfate attack when the concrete specimen was exposed to the wetting and drying cycles. It can be concluded that the use of 10 to 40% RHA effectively decreased the penetration depth (charge passed) in the concrete under sulfate attack.